PERILAKU CONE ALUMINUM TIPIS DENGAN SUDUT YANG BERBEDA DALAM MENYERAP ENERGI IMPAK - Witono Hardi (Fakultas Teknik Universitas Khairun, 2018)
The use of thin-walled structures as energy absorbers has been widely known and applied in various fields. Thin-walled structures have the ability to absorb energy very well at various levels of impact speed. In this study, an analysis of the behavior of thin-walled structures with aluminum cone-shaped was carried out. This structure has a length of 200 mm thickness of 2 mm with one end whose diameter is left to remain 50 mm and the other end is made varied; 50 mm, 64 mm, 84 mm, 104 mm and 124 mm. A pounder made of cube-shaped steel measuring 15 cm x 15 cm x 15 cm weighing 26.49 kg pounding the specimen at a speed of 10 m / s so that the kinetic energy is received is 1324.7 Joules. Deformation with certain patterns in thin-walled structures and the results of the simulation obtained are total deformation, bending pattern, and energy per unit length. From the five specimens, it was found that the thin tube had a longer deformation than the cone shape. But the cone's ability to absorb more energy is indicated by the amount of energy per unit length.